Heart and Sell - Levitin, Shari (Ascent Audio, 2019)
Are you making it difficult for your potential customers to buy from you? Today's buyers are overloaded-overwhelmed by too much information and suffering from decision fatigue. Across industries, customers are delaying purchasing decisions or even choosing to stick with the status quo so they can avoid the dreaded "sales process." In response, many sales professionals are overcompensating with behaviors that are either too accommodating or that create high pressure-and alienating potential buyers in the process. How can you reconcile your need to meet sales targets with the customer's desire for a heartfelt, authentic sales approach? Author Shari Levitin, creator of the Third-Level Selling system, offers a dynamic framework for effective selling in the Digital Age. Unlike other sales books that focus on abstract tips or techniques, Heart and Sell offers a science based real-world approach that will help you dramatically increase your sales-regardless of your level or industry.